Learners’ attitudes and perspectives towards English pronunciation abilities with different religious backgrounds in Thailand - Rahmah Bakoko; Budi Waluyo; Kritsadee Songkhai (Universitas Syiah Kuala, 2023)
A plethora of studies has examined EFL learners’ attitudes towards and perceptions of English pronunciation, yet little has been discussed about the influence of religious backgrounds on one’s pronunciation abilities, especially in the Thai context. This study aims to extend the research area by studying Buddhist and Muslim EFL learners’ attitudes and perspectives about their English pronunciation abilities in Thailand. Using a mixed-method design, it collected survey data from 60 undergraduate students (50% Buddhist, 50% Muslim) at a university in south Thailand. An English pronunciation test was conducted to gather data on the students’ English pronunciation performances. The quantitative findings revealed that Buddhist and Muslim Thai EFL learners possessed moderate levels of attitudes towards their English pronunciation and perceived indirect influences of their religion on their English pronunciation. Although the learners’ attitudes and perceptions were connected, they were not significant predictors of their actual English pronunciation. Religion and gender had no direct impact on the learners’ attitudes; however, their frequent religious practices have led to the awareness that students from some religious backgrounds can have an advantage in pronouncing some English sounds, letters, or words over their friends with a different religion. The results of this research also suggest that there is much more to be learned about the effects and contributions of religious backgrounds on learners’ English pronunciation among learners.